STRENGTHENING THE CAPACITY OF TEACHERS IN INTRODUCING INCLUSIVE BASIC LITERACY IN EARLY CHILDREN EDUCATION - Khosiah Khosiah; Dewi Rohiani; Raden Sudarwo; Khaerul Anam; Sintayana Muhardini (JCES (Journal of Character Education Society), 2022)
Abstrak: Pengenalan literasi sangat penting bagi anak PAUD terutama bagi anak-anak yang memiliki hambatan belajar. Oleh karena itu seorang guru harus memberikan layanan yang tepat sesuai kebutuhan anak. Salah satu upaya yang dilakukan melalui pengenalan literasi dasar mulai dari jenjang PAUD sebagai prasekolah yang menyiapkan anak-anak siap untuk belajar dijenjang Sekolah Dasar (SD).  Pelatihan  ini bertujuan untuk melatih guru Pendidikan Anak Usia Dini (PAUD) agar guru dapat mengenali kendala atau kesulitan belajar anak sejak dini, dapat menerapkan cara membangun pola pikir berkembang pada guru dan anak, serta dapat menerapkan pembelajaran literasi yang inklusif sesuai karakteristik anak yaitu belajar sambil bermain. Pelatihan ini dilaksanakan di TK Islam Al-Barokah Desa Kalijaga Tengah Kecamatan Aikmel.  Metode yang diterapkan dalam pelatihan ini ialah curah pendapat, diskusi kelompok, penugasan, praktik dan simulasi.  Berdasarkan hasil kegiatan pelatihan yakni  guru dapat memahami dan menerapkan penggunaan instrument untuk mengenali kesulitan belajar anak melalui kegiatan praktik langsung; guru dapat mengenali pola pikirnya sendiri melalui kegiatan praktik menjawab angket yaitu apakah guru sudah memiliki pola pikir yang berkembang (growt mindset) atau pemikiran kaku (fix mindset), serta guru dapat menerapkan kegiatan pembelajaran literasi inklusif yang menyenangkan melalui kegiatan praktik dan simulasi.Abstract: The introduction of literacy is very important for PAUD (Pendidikan Anak Usia Dini/Early Children Education) children, especially for children who have learning disabilities. Therefore, a teacher must provide appropriate services according to the needs of children. One of the efforts made is through the introduction of basic literacy starting from the PAUD level as preschool which prepares children to be ready to learn at the SD (Sekolah Dasar/Elementary School) level. This training aims to train Early Childhood Education (PAUD) teachers so that teachers can recognize obstacles or difficulties in children's learning from an early age, can apply ways of building a developing mindset for teachers and children, and can apply inclusive literacy learning according to children's characteristics, which is learning by doing. play or vice versa. This training was carried out at the Al-Barokah Islamic Kindergarten, Central Kalijaga Village, Aikmel District. The methods applied in this training are brainstorming, group discussions, assignments, practice and simulations. Based on the results of the training activities, teachers can understand and apply the use of instruments to identify children's learning difficulties through direct practical activities; teachers can recognize their own mindset through practical activities in answering questionnaires, whether the teacher already has a growth mindset or a fixed mindset, and teachers can apply fun inclusive literacy learning activities through practical activities and simulations.